Optimization of Childbirth Time Phase I Using MicrocontrollerBased Nipple Stimulation - Yanik Purwanti; Arief Wisaksono; Muhammad Iqbal (PT. Anagata Sembagi Education, 2024)
Background: The first stage of labor often takes a long time and causes discomfort forthe mother, so methods are needed to accelerate it. This study aims to evaluate theeffectiveness of microcontroller-based nipple stimulation in accelerating the laborprocess by stimulating the release of the hormone oxytocin which increases uterinecontractions and accelerates cervical opening. Microcontroller technology is used toensure the stimulation is done automatically and measured according to the mother'sphysiological needs. This study involved two groups, namely the group that receivedstimulation and the control group that did not receive stimulation. The results showedthat the stimulated group experienced shorter labor times than the control group andwere less likely to require medical interventions such as induction with drugs.Methods: Close monitoring is still required to ensure safety, especially regarding therisk of uterine hyperstimulation that may affect the condition of the mother and fetus.Further research is needed to test the long-term effectiveness and safety of this methodbefore it is widely applied in obstetric practice.Results: Based on the total library, 600 were identified and as many as 100 additionalarticles were identified. A total of 630 studies failed to meet the inclusion criteria and 70articles were read in their entirety, so that as many as 11 publications were used asreferences.Conclusion: Microcontroller-based nipple stimulation offers an innovative solution thatcan improve the efficiency of labor while providing a better quality of health care.Keywords : First Period of Labor, Medical Technology, Microcontroller, Nipple Stimulation,Time Efficiency